Identification of New Genes and Loci Associated With Bone Mineral Density Based on Mendelian Randomization - Liu, Yijun; Jin, Guang; Wang, Xue; Dong, Ying; Ding, Fupeng (Frontiers in Genetics, 2021)
Bone mineral density (BMD) is a complex and with highly hereditary which leads to osteoporotic fractures. It has been estimated that the hereditary probability is about 85%. BMD has been reported to be associated with both common and rare variants, and numerous loci related to BMD have been identified by genome-wide association studies (GWAS). We systematically integrated two types of omics data, expression quantitative trait loci, as known as eQTL data and GWAS summary statistical data, applying a SMR analysis to investigate new genes and loci associated with BMD. By the summary data integrated of GWAS and eQTL, we identified 12,477 SNPs regulating 564 genes which are associated with BMD. These genetic predictors we detected could make a contribution in the identification of individuals with the risk of BMD and play an important role in understanding the pathophysiology of BMD.